ITMIG 2017—Dr. Andreas Rimner: expertise, equipment, and experience are critical prerequisites in intraoperative radiotherapy - Mai, Taoli (Mediastinum; Vol 2 (January 2018): Mediastinum, 2018)
On Sep 23, the 8th International Thymic Malignancy Interest Group Annual Meeting (ITMIG 2017) held in Torino, Italy, successfully ended after a dense 3-day agenda blending a superb scientific and educational program, with over 150 participants in the field from more than 20 countries or regions.